2000
DOI: 10.1046/j.1524-475x.2000.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Incisional wound healing in transforming growth factor‐β1 null mice

Abstract: Expression of endogenous transforming growth factor-beta1 is reduced in many animal models of impaired wound healing, and addition of exogenous transforming growth factor-beta has been shown to improve healing. To test the hypothesis that endogenous transforming growth factor-beta1 is essential for normal wound repair, we have studied wound healing in mice in which the transforming growth factor-beta1 gene has been deleted by homologous recombination. No perceptible differences were observed in wounds made in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 52 publications
3
52
2
Order By: Relevance
“…Indeed, the use of genetically modified mice for wound healing studies recently revealed crucial roles for several growth factors and cytokines in the repair process (Table 4). For example, these studies have demonstrated an inhibitory effect of TGF-␤ on wound reepithelialization (2,12,66,149), an important role of FGF receptor signaling in this process (292), and a role of activin in granulation tissue formation and scarring (192,286). In the latter case, the phenotype was more pronounced in a CD1 background compared with a B6D2F2 background (Werner, unpublished data), demonstrating the importance of the genetic background for the outcome of the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of genetically modified mice for wound healing studies recently revealed crucial roles for several growth factors and cytokines in the repair process (Table 4). For example, these studies have demonstrated an inhibitory effect of TGF-␤ on wound reepithelialization (2,12,66,149), an important role of FGF receptor signaling in this process (292), and a role of activin in granulation tissue formation and scarring (192,286). In the latter case, the phenotype was more pronounced in a CD1 background compared with a B6D2F2 background (Werner, unpublished data), demonstrating the importance of the genetic background for the outcome of the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Many animal models of impaired wound healing have shown that reduction of endogenous TGF-␤1 in the wound bed underlies the defective repair process. This concept, however, has recently been questioned, because TGF-␤1 -/-and Smad3 -/-null mice showed accelerated wound healing and a reduction in the area of granulation tissue (Ashcroft et al, 1999;Koch et al, 2000). The findings may be explained in terms of the function of different TGF-␤ isoforms (O'Kane and Ferguson, 1997).…”
Section: (D) Wound Healingmentioning
confidence: 99%
“…However, in vivo data do not fully support such a stimulatory role of TGF-β signalling. Thus, mouse null mutants for Tgfb1 or the TGF-β-regulated transcription factor Smad3 show accelerated, rather than impaired wound closure (Ashcroft et al, 1999;Koch et al, 2000). This paradoxical result has been proposed to be due to concomitant and predominant effects of TGF-β signalling to suppress keratinocyte proliferation, which might counteract a direct stimulatory effect on epidermal migration (Ashcroft et al, 1999;Barrientos et al, 2008;Sivamani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%